Republic of Congo Poverty Assessment Report : Education, Jobs and Social Protection for a Sustainable Reduction of Poverty - World Bank Group (World Bank, Washington, DC, 2017)
This poverty assessment analyzes recent trends in monetary and nonmonetary aspects ofpoverty and economic vulnerability in the Republic of Congo (ROC), based on two nationallyrepresentative and broadly comparable household expenditure surveys conducted bythe National Institute of Statistics (NIS) in 2005 and 2011. The study determines the drivers ofpoverty reduction by systematically looking at demographic, labor, and human capital dimensions.The report also discusses cross-cutting issues relevant for poverty reduction, such as servicedelivery, marginalization of autochthons, and others. This study aims to provide policy makerswith the knowledge needed to improve the effectiveness of their programs to reduce and finallyeradicate extreme poverty in the Republic of Congo.